Seven years of progress in determining fungal diversity and characterization of fungi isolated from the Japanese Experiment Module KIBO, International Space Station. (19th August 2021) - Satoh, Kazuo; Alshahni, Mohamed Mahdi; Umeda, Yoshiko; Komori, Aya; Tamura, Takashi; Nishiyama, Yayoi; Yamazaki, Takashi; Makimura, Koichi
Abstract: The International Space Station (ISS) is a closed facility that orbits the earth carrying not only its crew but also microorganisms. We have participated in microbiota analysis projects for the Japanese Experiment Module KIBO (ISS; operations nomenclature: Microbe‐I, II, III, and IV) and were in charge of fungal screening. The interior of KIBO was sampled using swabs and microbe detection sheets (MDSs) for fungal detection. The dominant genera obtained by culture were Aspergillus and Penicillium . DNA analyses of the fungal biota using a clone library showed that KIBO was dominated by Malassezia, a fungal inhabitant of human skin. Three fungal species, Aspergillus sydowii, Penicillium palitans, and Rhodotorula mucilaginosa, which grew under microgravity in KIBO were observed under a field emission‐scanning electron microscope on the ground. No novel phenotypic characteristics were noted. The results of antifungal susceptibility testing of all isolates did not differ significantly from previous reports of corresponding fungi. In Microbe‐I (August 2009), MDSs were culture negative, while in the next stages the CFU of MDSs were 10 for Microbe‐II (February 2011), 24 for Microbe‐III (October 2012), and 151 for Microbe‐IV (February 2015). These results indicated that fungi inside KIBO are increasing and expanding over time, and therefore continuous surveillance is crucial.